FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN DI HOTEL TRAVELODGE BATAM - Triza Articia Gennie; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Customer loyalty is the engine of the success of a business. Loyalty is an attitude and behavior that indicates a repeat purchase of an item or service. In building and increasing customer loyalty, companies must pay attention to the factors that. This study aims to determine how much influence the satisfaction, emotional bonding, trust, choice reduction and habit factors and history with the company have taken from G. Zikmund's theory (2007: 72) and what factors are most influential and less influential on customer loyalty in Batam Travelodge Hotel. The population in this study were all guests who had stayed at Travelodge Batam Hotel while the samples taken were 100 guests who had stayed more than once at Travelodge Batam Hotel using purposive sampling technique. Data was collected using observation techniques, interviews and Likert scale model questionnaires calibrated using validity test and reliability test. The classic assumption test uses the normality test, multicollinearity test and heteroscedasticity test. Based on the research, it was found that there was a positive effect of X variable on Y variable as indicated by the results of linear regression analysis Y = 1.780 + 1.389 + 0.992 + 1.126 + 0.909 +0,898. The value of determination coefficient (R2) is 80.1% and the remaining 19.9% is influenced or explained by other variables not included in this regression model. Keywords: Service Quality, Customer Satisfaction, Customer Loyalty